2017
DOI: 10.3329/birdem.v8i1.35038
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and Hepatitis C Virus Infection among End Stage Renal Disease Patients on Maintenance Hemodialysis, Their Family Members and Dialysis Staffs - A Prevalence Study

Abstract: Background: Hepatitis B (HBV) and hepatitis C virus (HCV) infection is common among patients on maintenance hemodialysis (MHD). This study was undertaken to observe prevalence of hepatitis B and C infection in hemodialysis patients, their family members and dialysis staffs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Data on individuals specifically involved in the management of chronic HBV patients or its sequelae would be more useful in this regard. A 40-sample study found a rate of 0% prevalence among hemodialysis staff [ 51 ], while other studies have reported rates as high as 15%. This indicates the role of work environment, adherence to laboratory safety protocols and the attendant risk of exposure in determining HBV prevalence among the healthcare personnel and data regarding work history and other relevant factors should be collected to aid subsequent interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Data on individuals specifically involved in the management of chronic HBV patients or its sequelae would be more useful in this regard. A 40-sample study found a rate of 0% prevalence among hemodialysis staff [ 51 ], while other studies have reported rates as high as 15%. This indicates the role of work environment, adherence to laboratory safety protocols and the attendant risk of exposure in determining HBV prevalence among the healthcare personnel and data regarding work history and other relevant factors should be collected to aid subsequent interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%